Pesticide-free management of insect pests in vegetable production - Kodandaram, M. H.; Halder, Jaydeep; Rai, A. B.; Singh, B. (Indian Horticulture, 2019)
Eco-friendly pest control involves the use of cultural methods, sex pheromone, biopesticides, and bioagents. Use of these non-chemical methods helps in keeping the pest below economic threshold levels, maximizing the crop protection, minimizing pesticide residues in vegetables and reducing hazards in our environment. They help in conserving ecological equilibrium and fit well in IPM, reducing the cost of crop protection inputs.